Pricing of innate and discretionary accruals in Australian debt. (30th November 2011) - Aldamen, Husam; Duncan, Keith
Abstract This paper addresses the conflicting evidence on the role of accruals in debt pricing. We show that the two subcomponents of accruals quality, innate and discretionary accruals, both impact the debt pricing. Higher innate accruals increases cost of debt, consistent with the prior evidence (Francis, 2005; Gray, 2009). However, we also find that higher discretionary accruals reduce the cost of debt. This contrasts with the prior evidence of a positive association between discretionary accruals and cost and debt (Francis, 2005), and no association (Gray, 2009). We show that noisy measurement of cost of debt reconciles these results.